Erotica Romana - Goethe, Johann Wolfgang von, 1749-1832 (Salt Lake City, UT : Project Gutenberg, 2005)
"Erotica Romana" by Johann Wolfgang von Goethe is a collection of 24 elegiac poems written during the late 18th century. The work draws inspiration from classical Roman poets such as Tibullus and Catullus, exploring themes of love, desire, and beauty within the scenic backdrop of Rome. The text is characterized by a sensuous and introspective tone, reflecting Goethe's experiences and contemplations during his time in Italy. The poems within "Erotica Romana" present a rich tapestry of romantic exploration, featuring a narrator who navigates both the physical and emotional landscapes of love. The speaker waxes poetic about the charms of his beloved, recounts the pleasures of their clandestine encounters, and contemplates the nature of passion itself. The narrative oscillates between idealization and earthly desire, intertwining mythological references with personal reflection. Through vivid imagery and lyrical language, Goethe captures the intoxicating essence of love, revealing the complexities of attraction while celebrating the joys of intimate connection. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Roman_Elegies
Release date is 2005-04-01
Produced by Harry Haile, Mike Pullen, and David Widger
Keywords: German poetry -- Translations into English